RANCANGAN ATRAKSI WISATA EDUKASI DI PAON BALI INSTITUT PARIWISATA DAN BISNIS INTERNASIONAL - Agung Istri Ari Parwati, Anak; Sabda Jayendra, Putu; Darsana, I Made (Berajah Journal, 2024)
Bali Island, as a premier tourist destination, offers various potentials, including educational tourism that combines recreation and learning. One such potential location is Paon Bali, a traditional Balinese kitchen complex serving as a learning laboratory at the International Institute of Tourism and Business. This study aims to design educational tourism attractions based on culture and culinary aspects at Paon Bali. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation studies, then analyzed with Miles and Huberman's Interactive Data Analysis Model. The findings present the design of attractions such as Tour de Paon Bali, selfie activities, traditional games, cooking classes, culinary review sessions, and cooking competitions, which can be aligned with academic programs on campus. This study supports sustainable educational tourism attractions based on Community-Based Tourism (CBT) in a consistent and continuous manner.